Copper-on-copper homoepitaxy studied by infrared spectroscopy of adsorbed CO. - Tobin, Roger G.; Hancock, Michael.; Fein, Casey. (Tufts University. Tisch Library., 2017)
Infrared spectroscopy of adsorbed CO was used to characterize the dependence of surface structure on deposition temperature during homoepitaxial growth on Cu(100) Intensity borrowing due to dipole coupling greatly enhances the absorption signal due to defect-bonded CO, making it possible to detect and quantify defect concentrations at the level of a few percent. For deposition temperatures between 300 and 400 K, the defect density increases slightly with decreasing deposition temperature but remains below 2%. There is a sharp increase in defect density, up to 5%-6%, as the deposition temperature is decreased from 300 to 250 K. At lower deposition temperatures, there is some sign of a leveling off in defect density, but the IR absorption spectrum becomes so broad that meaningful analysis becomes impractical, while visible degradation of the low-energy electron diffraction pattern indicates worsening surface order. No indication of "re-entrant" ordering at low temperatures was observed for deposition temperatures down to 150 K.